"It's Not Just Us . . . We Ain't Doin' It Alone": Development of the Solution-Focused Wellness for HIV Intervention for Women. Issue 1 (January 2020) - Yates, Helen Taylor; Choi, Y. Joon; Beauchemin, James D.
To address health disparities in HIV care for women, we developed Solution-Focused Wellness for HIV (SFWH), an evidence-based intervention that capitalizes on strengths to improve overall wellness. SFWH utilizes solution-focused brief therapy, a salutogenic wellness approach and HIV research with women. We created an intervention manual and recruited ( N = 6) women living with HIV to provide expert client feedback through focus groups. The findings included themes of relationships with children and other family members, physical accommodations, antiretroviral therapy information, and improving the accessibility of the intervention. The SFWH intervention for women was feasible to deliver and positively received by the participants. We adapted the SFWH manual to incorporate our findings, and a quantitative study is planned to evaluate the effectiveness of the intervention.